2012
DOI: 10.1371/journal.pone.0047445
|View full text |Cite
|
Sign up to set email alerts
|

Basketball Teams as Strategic Networks

Abstract: We asked how team dynamics can be captured in relation to function by considering games in the first round of the NBA 2010 play-offs as networks. Defining players as nodes and ball movements as links, we analyzed the network properties of degree centrality, clustering, entropy and flow centrality across teams and positions, to characterize the game from a network perspective and to determine whether we can assess differences in team offensive strategy by their network properties. The compiled network structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 15 publications
7
123
0
6
Order By: Relevance
“…Briefly, it is possible to identify that soccer have been well studied by using network approach. Nevertheless, such situation it is not similar in other team sports such as basketball (Bourbousson, Poizat, Saury, & Seve, 2010;Fewell, Armbruster, Ingraham, Petersen, & Waters, 2012). In the case of under-18 French basketball players it was found small mutual forms of interactions and suggested that the coordination networks of the team were built on local coordination's chaining together in such a way as to not necessarily form a single unit (Bourbousson et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Briefly, it is possible to identify that soccer have been well studied by using network approach. Nevertheless, such situation it is not similar in other team sports such as basketball (Bourbousson, Poizat, Saury, & Seve, 2010;Fewell, Armbruster, Ingraham, Petersen, & Waters, 2012). In the case of under-18 French basketball players it was found small mutual forms of interactions and suggested that the coordination networks of the team were built on local coordination's chaining together in such a way as to not necessarily form a single unit (Bourbousson et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…In the case of under-18 French basketball players it was found small mutual forms of interactions and suggested that the coordination networks of the team were built on local coordination's chaining together in such a way as to not necessarily form a single unit (Bourbousson et al, 2010). By other hand, in a study that used data from NBA first round play-offs, it was showed a star pattern in the Bulls team who inbound only to the Point Guard at 60% and for which most passes were between the Point Guard and other players (Fewell et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Social network theory suggests that highly clustered networks are more effective as information conduits because they improve the ability of collaborating physicians to share information and develop innovative protocols for treatment. 18,19 To the extent that clustering promotes these different forms of teamwork, we hypothesized that it may also lead to improved surgical outcomes.…”
Section: Characterizing the Level Of Physician Teamwork In A Health Smentioning
confidence: 99%
“…One way to evaluate this is by quantifying the frequency of triangles [54] within the BPN. Such an approach has been adopted in identifying relative involvement of players in Basketball [55]. This can also be extended to study player involvement in Soccer as well.…”
Section: Resultsmentioning
confidence: 99%